Flow induced vibration of a square cylinder with high scruton number - Ismail, Mohamad Hafiz (2015)
Flow over a square cylinder is numerically studied to understand the effect of reduced velocity to the transverse oscillation under the influence of high Scruton number elastic system of 4.316. For low reduced velocities, the transverse oscillation behavior can be grouped in the initial branch region. In this region, the motion is mainly controlled by the lift fluctuation. For intermediate reduced velocities, the transverse oscillation behavior is grouped in the lower branch region. In this region, its natural frequency slowly becomes significant. For high reduced velocities, the galloping region is observed. In this region, the natural frequency dominated the shape of the amplitude oscillation.